Effects of Teasing in Physical Education Classes, Self-efficacy, and Physical Activity on Adolescents’ Self-esteem El efecto del hostigamiento en las clases de educación física, la autoeficacia y la actividad física en la autoestima de los adolescentes - De Marco J.C.P.* (2023)
© 2023 Colegio Oficial de Psicologos de Madrid. All rights reserved.Objective: To investigate the differences between boys and girls in the present variables, and assess the possible associations between self-esteem and teasing in school physical education classes, self-efficacy, and physical activity among adolescents. Method: The sample included 944 adolescents aged 14 to 19 years (mean =16.52, SD = 1.12, 53.6% male), enrolled in public high schools in Florianópolis, Santa Catarina, Brazil. Information was collected on age, body mass index, physical activity level, self-efficacy, teasing experiences in physical education classes, and self-esteem (dependent variable). Self-esteem was assessed using the Rosenberg Self-esteem Scale. Results: Adolescents had a mean self-esteem score of 28.71 (out of 40), with boys having higher scores than girls (29.66 vs. 27.61, p < .001). In both sexes, adolescents who reported lower levels of teasing in physical education classes had higher self-esteem. Boys with high self-efficacy and higher levels of physical activity had higher self-esteem scores. Conclusion: Experiencing teasing in school physical education classes was a predictor of self-esteem in adolescents of both sexes, and self-efficacy and physical activity were predictors of self-esteem in boys.